Melatonin Enhances Seed Germination and Seedling Growth of Medicago sativa Under Salinity via a Putative Melatonin Receptor MsPMTR1 - Yu, Ruonan; Zuo, Tiantian; Diao, Pengfei; Fu, Jiabin; Fan, Yanyan; Wang, Yue; Zhao, Qiqi; Ma, Xuesong; Lu, Wenting; Li, Aoga; Wang, Ru; Yan, Fang; et al. (Frontiers in Plant Science, 2021)
Alfalfa (Medicago sativa L.) is an important forage crop, and salt stress is a major limiting factor on its yield. Melatonin (MT) is a multi-regulatory molecule in plants. We showed that basal MT content was positively correlated with salt tolerance degree of different alfalfa varieties. MT and its precursor 5-HT fully recovered seed germination while partially ameliorated seedling growth of salt stressed alfalfa. 5-HT showed some divergent effects from MT as regards to growth amelioration under salinity. Salt stress caused stunted plant growth in soil culture, while MT ameliorated it by elevating plant height, fresh weight, branching number and chlorophyll content. Silencing of a putative MT receptor MsPMTR1, which was shown to be membrane localized, abolished ameliorative effects of MT on salt stressed alfalfa seedling growth, while overexpression of MsPMTR1 improved plant growth under salt stress. RNA-seq analysis showed that nine pathway genes were specifically induced by MT treatment compared with salt stress. These MT-responsive DEGs include basal metabolic pathway genes, such as“ribosome, elongation factor”, “sugar and lipid metabolism” and “photosynthesis” and stress related genes encoding“membrane integrity” related proteins, heat shock protein, peroxidase/oxidoreductase and protease. Several abiotic stress response related genes such as DRE, ARF, HD-ZF, MYB and REM were repressed by NaCl treatment while were induced by MT treatment. In summary, we demonstrated the importance of MsPMTR1 in MT-mediated salt tolerance in alfalfa, and we also analyzed the regulatory mechanism of MT during alfalfa seed germination under salt stress.